Evaluation of the cooling effect provided by a green façade as nature-based system for buildings. (October 2021) - Convertino, Fabiana; Vox, Giuliano; Schettini, Evelia
Abstract: A strategy to make cities greener involves the use of green infrastructures. In this context, green façades applied to vertical envelope of buildings are one of the most promising technologies. Their contribution is particularly significant as passive cooling systems for buildings. Green façades allow to decrease air and surfaces temperatures mainly by canopy evapotranspiration and shading. Such processes are strongly influenced by environmental conditions and canopy characteristics. Aim of this research was to model and evaluate evapotranspirative and shading effects. Data recorded on an experimental prototype of building equipped with green façade were used for model development and assessment. Canopy characteristics, as leaf area index in vertical greening, were defined. Evapotranspiration was both measured with a load cell and evaluated through the green layer energy balance. The goodness-of-fit of the models was assessed by statistical indices. The models using Penman-Monteith and Deardorff formula, in summer, recorded average values of root mean square error equal to 12.48 W m −2 and to 14.61 W m −2, respectively. Plant coefficients useful for the application in vertical greening of the standardized evapotranspiration reference equation were defined. These were equal to 1.3 and 2.0 for Rhyncospermum Jasminoides in summer and spring, respectively. The daily overall cooling effect in summer, due to evapotranspiration and shading, was equal, on average, to 16.2 MJ m −2 of wall surface. Shading contributed about twice as much as the evapotranspiration. The findings of this research can be a useful contribution to writing routines of building energy models expressly developed for green façades. Graphical abstract: Image 1 Highlights: Cooling effect in green façade is modelled. Experimental data are collected on a prototype of building with green façade. Evaluation of plant LAI and radiometric characteristics. Evapotranspiration latent heat exchange is measured and modelled. Evaluation of the shading effect of green façade.